Are circulating microRNAs suitable for the early detection of malignant mesothelioma? Results from a nested case–control study - Daniel Gilbert Weber; Alexander Brik; Swaantje Casjens; Katarzyna Burek; Martin Lehnert; Beate Pesch; Dirk Taeger; Thomas Brüning; Georg Johnen; the MoMar study group (BMC Research Notes, 2019)
Abstract Objective Malignant mesothelioma is an aggressive cancer of the serous membranes. For the detection of the tumor at early stages non- or minimally-invasive biomarkers are needed. The circulating biomarkers miR-132-3p, miR-126-3p, and miR-103a-3p were analyzed in a nested case–control study using plasma samples from 17 prediagnostic mesothelioma cases and 34 matched asbestos-exposed controls without a malignant disease. Results Using prediagnostic plasma samples collected in median 8.9 months prior the clinical diagnosis miR-132-3p, miR-126-3p, and miR-103a-3p revealed 0% sensitivity on a defined specificity of 98%. Thus, the analyzed miRNAs failed to detect the cancer in prediagnostic samples, showing that they are not feasible for the early detection of malignant mesothelioma. However, the miRNAs might still serve as possible markers for prognosis and response to therapy, but this needs to be analyzed in appropriate studies.